Increasing Trend of Clinical Laboratory Testing at Gelephu Central Regional Referral Hospital, Bhutan - Chhetri, Vishal; Yangchen, Karma; Dawa, Chenga (International Journal of Innovative Research in Medical Science, 2018)
Bhutanese population have access to both traditional and modern medicine. The record published in Annual Health Bulletin (AHB), Ministry of Health (MoH) recorded the number of people seeking modern medicine has drastically escalated over the past few years. Gelephu based Central Regional Referral Hospital (CRRH), established in 1960’s, sees the second highest number of outpatient department OPD cases in the country. As a result the number of clinical laboratory testing has also increased over the time. The ratio of annual OPD attendance and annual laboratory test recorded at the medical record and AHB depicted at the ratio of 1:1 until 2013 and the ratio increased to 1:1.9 in 2017, significant at p<0.05. The annual total laboratory test increased from n=118567 in 2013 to n=234869 in 2017, with almost an increase by average of 2% annually. The increasing number of test order, increases the probabilities for error. Hence, laboratory quality system is of paramount importance. The introduction of automation in Biochemistry (2014) and Hematology (2015), has significantly reduced analytical errors and has generated reliable, and quality assured reports. No reports have been published until now from CRRH to indicate the increasing clinical laboratory tests. Therefore, the data analysis from this study will present the ever increasing annual laboratory testing conducted at CRRH and would also provide the national medical procurement and supply division with information critical for annual supply forecasting.